2011
DOI: 10.1007/s00031-011-9131-z
|View full text |Cite
|
Sign up to set email alerts
|

Simple locally compact groups acting on trees and their germs of automorphisms

Abstract: Automorphism groups of locally finite trees provide a large class of examples of simple totally disconnected locally compact groups. It is desirable to understand the connections between the global and local structure of such a group. Topologically, the local structure is given by the commensurability class of a vertex stabiliser; on the other hand, the action on the tree suggests that the local structure should correspond to the local action of a stabiliser of a vertex on its neighbours. We study the interpl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 22 publications
2
66
0
Order By: Relevance
“…Here we give an outline of their construction (see Section 4 for precise definitions). Every finite permutation subgroup These groups appear in [13], where a careful study of the abstract commensurator group of self-replicating profinite wreath branch groups is carried out (we refer to [2] for an introduction to abstract commensurators of profinite groups). Let W k (D) be the closed subgroup of Aut(T d,k ) fixing pointwise the first level of T d,k and acting by an element of W (D) in each subtree rooted at level one.…”
Section: Introduction Almost Automorphism Groupsmentioning
confidence: 99%
“…Here we give an outline of their construction (see Section 4 for precise definitions). Every finite permutation subgroup These groups appear in [13], where a careful study of the abstract commensurator group of self-replicating profinite wreath branch groups is carried out (we refer to [2] for an introduction to abstract commensurators of profinite groups). Let W k (D) be the closed subgroup of Aut(T d,k ) fixing pointwise the first level of T d,k and acting by an element of W (D) in each subtree rooted at level one.…”
Section: Introduction Almost Automorphism Groupsmentioning
confidence: 99%
“…Let U+false( Alt (6)false) be the Burger–Mozes universal simple group for the alternating group on 6 elements with the usual permutation representation (see for a discussion of these groups). The group U+false( Alt (6)false) acts on the 6‐regular tree T6.…”
Section: Examplesmentioning
confidence: 99%
“…Just as with compact generation, discreteness is not a normal compression invariant, even if we restrict to compressions between non-abelian characteristically simple groups; cf. i∈Z Alt (5) and i∈Z Alt (5). There is a more general property that is close to discreteness and admits better preservation properties: An l.c.s.c.…”
Section: Quasi-discretenessmentioning
confidence: 99%
“…Neretin groups are also studied in [28], where it is shown that they do not contain a lattice, and the notation used here conforms with that paper. The papers [29], on abstract commensurators, and [30], on 'germs of automorphisms' are also relevant. Neretin's groups are also the inspiration for the simple groups acting on trees recently constructed in [31].…”
Section: Glöckner Bases This Decomposition On a Variation On ([18] Lementioning
confidence: 99%
“…Since abstract t.d.l.c. groups always contain a compact open, and hence commensurated, subgroup, they may be realised concretely as groups of commensurators quite generally, see [29,30,35]. Moreover, given any pair (G, H) such that H is a commensurated subgroup of G, a t.d.l.c.…”
Section: Computing In Tdlc Groupsmentioning
confidence: 99%